Antisocial media and algorithmic deviancy amplification: analysing the id of Facebook’s technological unconscious - Wood, Mark A. (Theoretical criminology, 2017)
Fight pages are user-generated Facebook pages dedicated to hosting footage of street fights and other forms of bare-knuckle violence. In this article, I argue that these pages exemplify an emergent and under-researched online phenomenon that may be termed antisocial media: participatory webpages that aggregate, publically host, and sympathetically curate footage of criminalized acts. To properly apprehend the implications of antisocial media for the mediation, distribution, and consumption of footage of criminalized acts, we must be attentive to the specificities of their architecture, their affordances and, increasingly, their personalization algorithms, which tailor the content a user receives to reflect their inferred preferences. This article therefore analyses the ‘technological unconscious’ of Facebook to demonstrate how the interactivity and personalization of the site’s information landscapes have the potential to reinforce or amplify fight page users’ often-harmful attitudes towards violence.